Data-driven Business Model Innovation - When is Decoupling Necessary? - Eriksson Taina; Nummela Niina; Heikkilä Marikka (Routledge, 2025)
This chapter investigates the issues related to data-driven business model innovation which relate them to the need of decoupling. More specifically, this study investigates how small- and medium-sized enterprises (SMEs) innovate new business by utilising data analytics techniques to improve their future competitiveness and resilience. This chapter adopts a “matched-pair” case study of two Finnish SMEs applying an inductive approach and data triangulation and uncovers the emergence of business model innovation in real time. Focal factors have led the SMEs to decouple the novel business from the established one and develop a parallel business model for the new offering of the studied SMEs. The findings have proved that in the case of SMEs, decoupling has been necessary for resilience building purposes. The key contribution of the study is in uncovering that forward firms’ strategies help managing multiple business models in SMEs when decoupling takes place.
Reconfiguration of business models and ecosystems: Decoupling and resilience